ECITRA: Digital X Culture - Mohamad Faizuan, bin Mat (National Art Gallery, 2019)
The Exhibition of Creativity, Innovation, and Technology in the Arts (eCITRA) is an initiative to elevate the cultural identity through the integration of digital technology. Besides, this exhibition hopes to bring audiences into the journey of an individual (artist) beliefs and cultures, as well as the ideation and conceptualisation stage of producing artworks: thoughts, sights, and emotions. Thus, this exhibition is an excellent platform for artists to explore the potential of these two elements through the process of research: the artistic praxis of embracing digital technology and cultures. This exhibition has invited artists from various disciplines, techniques, medium, styles and forms to rethink and transform present cultural understandings into newfangled artistic approaches. Although the critical discussion on digital artworks as a pure form of art is still ongoing, the use of digital technology is undeniably vital for many, especially for the artists. Thus, the discourse between critics and artists in this contemporary era should focus on delivering the right signs, symbols, and icons (messages) to the community (audiences), rather than focusing on the usage of gadgets and tools, provided that digital technology has so much to offer.